Censorship of electronic information in academic libraries - Catral, Aldwin B. (2002)
Computers have become the most versatile piece of equipment in history today. They make our tasks easier, allowing us to work more efficiently. They have integrated themselves to almost everything we do, from driving cars to making business transactions, from researching to leisure, and from music to literature to art. However, there has been growing concern with the effect of computers in today's society. Piracy and misinformation are just an example of these. The most prevalent issue is censorship.